The recognition of forest rights in Latin America: progress and shortcomings of forest tenure reforms - Pacheco, P.; Barry, D.M.; Cronkleton, P.; Larson, A.M. (2011)
Significant tenure reforms have taken place over public forestlands in the past 20 years in Latin America. These reforms differ from previous tenure reforms with respect to their origins and goals. In forest tenure reform, rights have being granted through a diversity of tenure arrangements, mainly to those already living in forests and to collectives rather than individuals, and with the potentially contradictory goals of promoting local well-being while conserving forests. These reforms face several challenges for achieving their goals and have resulted in ambiguous outcomes. We argue that outcomes for people and forests could be improved if, besides the simple recognition of rights to forests, greater attention is placed on aligning broader policy incentives to support community and smallholders efforts to manage their forests. We discuss the characteristics of forest tenure reform based on five cases, representing different tenure arrangements, in four countries in Latin America.